Bioactive glass composition as well as preparation method and application thereof
By modifying the surface of polyphenol compounds on calcium-phosphorus silicon-based bioactive glasses, a bioactive glass composition is formed, and the problem of blocking instability of bioactive glasses in the prior art under acid-resistant corrosion and mechanical wear conditions is solved, and the problem of blocking instability of bioactive glasses in the prior art is achieved. It provides better acid and wear resistance stability as well as enhanced biocompatibility and antibacterial effects.
Patent Information
- Application Number
- CN202411517125.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
In the desensitizer used for dentin-sensitive treatment, the sealing effect of existing bioactive glass is unstable under acid erosion and mechanical wear conditions, making it difficult to cope with complex oral environments.
By surface modification of calcium-phosphorus silicon-based bioactive glass with polyphenol compounds (such as gallatecatechin gallate, resveratrol, tannic acid), a bioactive glass composition is formed for dentin defects. Block.
During dentin repair, the acid resistance and wear resistance of the improved bioactive glass composition are improved, and the drug loading rate, biocompatibility, water solubility, bioactivity and antibacterial effects are also obtained. promote.
Smart Images

Figure CN119386046A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials and relates to a bioactive glass composition and a preparation method and application thereof. Background Art
[0002] Bioactive glass (BAG) is a type of material that can repair, replace and regenerate body tissues and form a bond between tissues and materials. BAG originally refers to silicate glass composed of basic components such as SiO2, CaO and P2O5, that is, calcium-phosphorus-silicon bioactive glass. The degradation products of bioactive glass can promote the production of growth factors, promote cell reproduction, enhance the gene expression of osteoblasts and the growth of bone tissue. It is the only artificial biomaterial that can form a bond with bone tissue and connect with soft tissue at the same time.
[0003] Dental diseases such as caries, wedge-shaped defects, and periodontal atrophy may expose dentin, cause dentin hypersensitivity, and affect the health and function of natural teeth. According to fluid dynamics theory, an effective way to treat dentin hypersensitivity is to block the dentinal tubules and promote the formation of reparative dentin. Desensitizing materials represented by bioactive glass have been developed as desensitizers or treatments for dentin hypersensitivity, but these treatments are effective in immediately blocking the dentinal tubules, but lack long-term sealing stability under conditions such as acid resistance and mechanical wear, and are difficult to cope with complex oral environments.
[0004] Polyphenols are a class of plant secondary metabolites with a special structure, which usually have one or more aromatic rings and contain one or more hydroxyl groups. These hydroxyl groups can be directly connected to the aromatic rings or connected to the aromatic rings through other carbon chains or functional groups. This structural feature makes polyphenols have good hydrophilicity and polarity, and they are easy to interact with other molecules in the body. It is an effective antibacterial agent that can bind to the bacterial cell wall, cause irreversible damage to the plasma membrane, interfere with its biosynthesis and dissolved oxygen reaction in water, and thus can effectively inhibit the growth of common oral bacteria and the formation of biofilms. Summary of the invention
[0005] The purpose of the present invention is to improve calcium phospho-silicon bioactive glass in a simple and low-cost manner so that it can be used as a desensitizer for treating dentin sensitivity and have a better blocking effect. To this end, the present invention provides a bioactive glass composition and its preparation method and application to solve this need in the art.
[0006] In one aspect, the present invention relates to a bioactive glass composition, comprising: a substrate, wherein the substrate is a bioactive glass;
[0007] The surface of the substrate is modified with polyphenol compounds.
[0008] Furthermore, in the bioactive glass composition provided by the present invention, the bioactive glass is calcium phospho-silicate bioactive glass.
[0009] Furthermore, in the bioactive glass composition provided by the present invention, the bioactive glass is copper-doped calcium-phosphorus-silicon bioactive glass.
[0010] Furthermore, in the bioactive glass composition provided by the present invention, the molar ratio of silicon, calcium, phosphorus and copper in the copper-doped calcium-phosphorus-silicon bioactive glass is 60-90:35-5:4:1-5.
[0011] Furthermore, in the bioactive glass composition provided by the present invention, the polyphenol compound is selected from at least one of epigallocatechin gallate, resveratrol and tannic acid.
[0012] On the other hand, the present invention relates to a method for preparing a bioactive glass composition, which comprises: dispersing the bioactive glass in an alkaline buffer solution, then dripping it into a solution of a polyphenol compound, and preparing the bioactive glass composition after the bioactive glass changes color.
[0013] Furthermore, in the method for preparing the bioactive glass composition provided by the present invention, the alkaline buffer solution is a tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 8-9.
[0014] Furthermore, in the method for preparing the bioactive glass composition provided by the present invention, the mass ratio of the bioactive glass to the polyphenol compound is 5:2-10.
[0015] In another aspect, the present invention relates to use of the bioactive glass composition in preparing a tooth desensitizing agent.
[0016] In another aspect, the present invention relates to the use of the bioactive glass composition in preparing a toothpaste additive.
[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0018] The present invention modifies the surface of the bioactive glass with a polyphenol compound, and shows a better sealing effect when used for dentin defect sealing. Not only the drug loading rate, biocompatibility, water solubility, biological activity and antibacterial effect of the bioactive glass are improved, but also the acid resistance stability and wear resistance stability of the sealing effect when used for dentin repair are also improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The photo of bioactive glass powder. A is BGNCu; B is BGNCu@EGCG.
[0021] Figure 2 The physicochemical characterization results of bioactive glass. A is the transmission electron microscope image of BGNCu; B is the transmission electron microscope image of BGNCu@EGCG; C is the X-ray diffraction spectrum of bioactive glass powder; D is the Fourier transform infrared absorption spectrum of bioactive glass powder.
[0022] Figure 3 Figure 2 is the EGCG loading rate and release curve of BGNCu@EGCG. A is the thermogravimetric analysis graph; B is the release curve of EGCG over time under different pH environments.
[0023] Figure 4 The results of the biocompatibility test of bioactive glass are shown in Figure 1. A shows the cell activity measurement of BGNCu and BGNCu@EGCG after co-culture with human dental pulp stem cells (HDPSCs) at different concentrations for 24 hours; B shows the hemolysis rate of BGNCu and BGNCu@EGCG after co-culture with rat red blood cells (RBCs) at different concentrations for 30 minutes.
[0024] Figure 5 The X-ray diffraction patterns of bioactive glass before and after immersion in simulated body fluid (SBF) for different time periods (1, 3, 7, and 14 days). A is the XRD pattern of BGNCu before and after mineralization after immersion in SBF for different time periods; B is the XRD pattern of BGNCu@EGCG before and after immersion in SBF for different time periods.
[0025] Figure 6The scanning electron micrographs of the sealing effect of BGNCu@EGCG as a desensitizer on dentinal tubules after one week of treatment. Among them, A is the dentinal tubules of the untreated group; B is the dentinal tubules treated with BGNCu; C is the dentinal tubules treated with BGNCu@EGCG; D is the dentinal tubules of the untreated group after soaking in 6% citric acid for 60 seconds; E is the dentinal tubules of the BGNCu group after soaking in 6% citric acid for 60 seconds; F is the dentinal tubules of the BGNCu@EGCG group after soaking in 6% citric acid for 60 seconds; G is the dentinal tubules of the untreated group after mechanical abrasion by brushing; H is the dentinal tubules of the BGNCu group after mechanical abrasion by brushing; I is the dentinal tubules of the BGNCu group after mechanical abrasion by brushing.
[0026] Figure 7 The results of bioactive glass nanoparticles inhibiting Streptococcus mutans. A is the image of the coated agar plate of the untreated group, BGNCu, BGNCu@EGCG and Streptococcus mutans co-cultured for 24 hours; B is the quantitative counting image of the colony forming units on the above plate.
[0027] Figure 8 The present invention is a scanning electron microscope image of the biofilm formed by Streptococcus mutans on dentinal tubules treated with the bioactive glass desensitizer prepared by the present invention. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are available on the market unless otherwise specified. The % in the following embodiments are all mass percentages unless otherwise specified. The ratios in the following embodiments are all mass ratios unless otherwise specified.
[0029] Example 1
[0030] This embodiment provides a preparation process of calcium phospho-silicate bioactive glass.
[0031] Calcium-phosphorus-silicon bioactive glass refers to silicate glass of the CaO-P2O5-SiO2 (45S) system, and its preparation methods include traditional molten bioglass and sol-gel bioglass. The temperature required for the preparation of molten bioglass is high, and high-temperature sintering can easily cause uneven material composition and reduce the biological activity of the material. Sol-gel bioglass has a simple preparation process, high purity, stable chemical composition, and high biological activity. This embodiment takes the sol-gel template method as an example to synthesize bioactive glass (BGN) using silicon source, calcium source, and phosphorus source.
[0032] The template is added to a mixed solvent of ethanol and water and stirred to obtain a uniform mixed solution, and a silicon source, a phosphorus source, and a calcium source are added in sequence to react fully until the reaction is complete, and the precipitate is washed with anhydrous ethanol and deionized water respectively, and then dried to obtain a precursor. The precursor is calcined to obtain BGN powder.
[0033] Exemplarily, the template agent is selected from at least one of dodecylamine, cetylpyridinium bromide, and cetyltrimethylammonium bromide.
[0034] Exemplarily, the silicon source is selected from at least one of ethyl orthosilicate, methyl orthosilicate, and tetraethoxysilane.
[0035] Exemplarily, the phosphorus source is selected from at least one of triethyl phosphate, tributyl phosphate, and phosphoric acid.
[0036] Exemplarily, the calcium source is selected from at least one of calcium nitrate, calcium chloride, and calcium bicarbonate.
[0037] Exemplarily, the calcination temperature is 650-750° C., and the sintering time is 3-5 hours.
[0038] Example 2
[0039] This embodiment provides a preparation process of copper-doped calcium phospho-silicon bioactive glass (BGNCu).
[0040] The preparation process is the same as that of Example 1, except that the silicon source, phosphorus source, calcium source and copper source are added in sequence and reacted fully until completion.
[0041] Exemplarily, the copper source is selected from at least one of copper nitrate and copper chloride.
[0042] Example 3
[0043] This embodiment provides a preparation process of a bioactive glass composition, the purpose of which is to use polyphenol compounds to perform surface modification or surface functionalization on bioactive glass.
[0044] The bioactive glass (BGN or BGNCu) is dispersed in an alkaline buffer solution and then added dropwise to a solution of a polyphenol compound (PP). After the bioactive glass changes color, a bioactive glass composition (BGN@PP or BGNCu@PP) is prepared.
[0045] Specifically, BGN or BGNCu is mixed with PP in an alkaline environment in the dark to prepare BGN@PP or BGNCu@PP.
[0046] Specifically, BGN or BGNCu is dispersed in a tris-hydroxymethylaminomethane hydrochloride solution (Tris-HCl) with a pH of 8 to 9, and is fully dispersed by ultrasound to serve as the first solution; PP is dispersed in deionized water, and is fully dispersed by ultrasound to serve as the second solution; the second solution is added dropwise to the first solution under light-proof conditions, and is continuously stirred for full reaction. The precipitate is washed with anhydrous ethanol and deionized water, respectively, and then dried to obtain BGN@PP or BGNCu@PP.
[0047] Exemplarily, the polyphenol compound is selected from at least one of epigallocatechin gallate (EGCG), resveratrol (Res), and tannic acid (TA).
[0048] Example 4
[0049] This example provides a preparation process of BGNCu@TA.
[0050] A mixed solvent of 20 mL of anhydrous ethanol (EtOH) and 6.25 mL of water was added to a 100 mL round-bottom flask and ultrasonically dispersed for 10 min to mix it evenly; then 1 g of dodecylamine (DDA) was added, the temperature was raised to 45 ° C and stirred for 15 min to fully dissolve it; then 0.5 mL of tetraethyl orthosilicate (TEOS) was added to the above mixed liquid twice with an interval of 15 min, and the reaction was carried out for 30 min; then 51 μL of triethyl phosphate (TEP) was dropped and continued to stir for 30 min; 0.317 g of calcium nitrate tetrahydrate was dissolved in 1 mL of water and added to the above mixed solution, and continued to stir for 3 h; 27 mg of copper nitrate trihydrate was dissolved in 0.5 mL of water and added to the above mixed solution, and continued to stir for 30 min; then, a blue precipitate was obtained by high-speed centrifugation, washed with anhydrous ethanol and deionized water for 3 times respectively, freeze-dried, placed in a muffle furnace, sintered at 650 ° C for 3 h, and finally BGNCu bioactive glass was obtained.
[0051] 20 mg of BGNCu particles and 40 mL of tris(hydroxymethylaminomethane) hydrochloride solution (Tris-HCl, pH 8.5) were added to a 100 mL round-bottom flask and ultrasonically dispersed for 10 min to mix them evenly. Subsequently, 10 mg of TA and 10 mL of water were weighed into a 15 mL centrifuge tube under light-proof conditions and ultrasonically dispersed for 10 min to mix them evenly. Under light-proof conditions, 10 mL of 1 mg / mL TA aqueous solution was dripped dropwise into 2 mg / mL BGNCu solution (Tris-HCl) and stirred continuously at room temperature for 3 h. Finally, the mixed solution was centrifuged to obtain a brown precipitate, which was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain BGNCu@TA nanoparticles.
[0052] Example 5
[0053] This example provides a preparation process of BGNCu@Res.
[0054] A mixed solvent of 5 mL of anhydrous ethanol (EtOH) and 1.5625 mL of water was added to a 50 mL round-bottom flask, and ultrasonic dispersion was performed for 10 min to mix the mixture. Then, 0.25 g of dodecylamine (DDA) was added, and the mixture was heated to 55 °C and stirred for 15 min to fully dissolve the mixture. Then, 0.125 mL of tetraethyl orthosilicate (TEOS) was added to the mixed liquid three times at intervals of 15 min, and the mixture was reacted for 30 min. Then, 12.75 μL of triethyl phosphate (TEP) was added dropwise, and the mixture was stirred for 15 min. Stir for 30 minutes; dissolve 0.07925g of calcium nitrate tetrahydrate in 0.25mL of water, add it to the above mixture, and continue stirring for 3 hours; dissolve 6.75mg of copper nitrate trihydrate in 0.5mL of water, add it to the above mixture, and continue stirring for 30 minutes; then, obtain a blue precipitate by high-speed centrifugation, wash it with anhydrous ethanol and deionized water for 3 times respectively, freeze-dry it, place it in a muffle furnace, and sinter it at 700°C for 5 hours to obtain BGNCu bioactive glass.
[0055] 5 mg BGNCu particles and 10 mL tris(hydroxymethylaminomethane) hydrochloride solution (Tris-HCl, pH 8.5) were added to a 50 mL round-bottom flask and ultrasonically dispersed for 10 min to mix them. Subsequently, 2.5 mg Res and 2.5 mL water were weighed into a 5 mL centrifuge tube under light-proof conditions and ultrasonically dispersed for 10 min to mix them. Under light-proof conditions, 2.5 mL 1 mg / mL Res aqueous solution was dripped dropwise into 2 mg / mL BGNCu solution (Tris-HCl) and stirred continuously at room temperature for 5 h. Finally, the mixed solution was centrifuged to obtain a brown precipitate, which was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain BGNCu@Res nanoparticles.
[0056] Example 6
[0057] This example provides a preparation process of BGNCu@EGCG.
[0058] A mixed solvent of 4 mL of anhydrous ethanol (EtOH) and 1.25 mL of water was added to a 20 mL round-bottom flask and ultrasonically dispersed for 5 min to mix it. Then, 0.2 g of dodecylamine (DDA) was added, and the temperature was raised to 60 ° C and stirred for 30 min to fully dissolve it. Then, 0.1 mL of tetraethyl orthosilicate (TEOS) was added to the mixed liquid twice with an interval of 30 min, and the reaction was carried out for 30 min. Then, 10.2 μL of triethyl phosphate (TEP) was dropped and stirred for 30 min. 0.0634 g of calcium nitrate tetrahydrate was dissolved in 0.5 mL of water and added to the mixed liquid, and the stirring was continued for 3 h. 5.4 mg of copper nitrate trihydrate was dissolved in 0.5 mL of water and added to the mixed liquid, and the stirring was continued for 30 min. Subsequently, a blue precipitate was obtained by high-speed centrifugation, washed with anhydrous ethanol and deionized water for 3 times respectively, freeze-dried, placed in a muffle furnace, and sintered at 750 ° C for 4 h to obtain BGNCu bioactive glass.
[0059] 4 mg of BGNCu particles and 8 mL of tris(hydroxymethylaminomethane) hydrochloride solution (Tris-HCl, pH 8.5) were added to a 20 mL round-bottom flask and ultrasonically dispersed for 10 min to mix them. Subsequently, 2 mg of EGCG and 2 mL of water were weighed into a 5 mL centrifuge tube under light-proof conditions and ultrasonically dispersed for 10 min to mix them. Under light-proof conditions, 2 mL of 1 mg / mL EGCG aqueous solution was dripped dropwise into the 2 mg / mL BGNCu solution (Tris-HCl) and stirred continuously at room temperature for 5 h. Finally, the mixed solution was centrifuged to obtain a brown precipitate, which was washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried to obtain BGNCu@EGCG nanoparticles.
[0060] Example 7
[0061] BGNCu@TA, BGNCu@Res and BGNCu@EGCG showed similar improvement effects. Therefore, this example takes BGNCu@EGCG prepared in Example 6 as an example to verify the effect of its surface modification.
[0062] Figure 1 This is a photo of the bioactive glass powder prepared by the present invention. Figure 1 A is a photo of BGNCu bioactive glass, which appears as a blue powder; Figure 1 B is a photo of BGNCu@EGCG bioactive glass, which appears as a brown powder.
[0063] Figure 2 The physical and chemical characterization results of the bioactive glass prepared by the present invention are as follows. Figure 2A and 2B are the transmission electron microscopy (TEM) images of BGNCu and BGNCu@EGCG, respectively. It can be observed that the former shows a monodisperse spherical morphology with a rough surface, while the TEM image of the latter clearly shows a monodisperse spherical morphology with a smooth surface, indicating that the coating process of EGCG on BGNCu is successful. Figure 2 C is the X-ray diffraction pattern (XRD) of the bioactive glass. It can be seen that both of them show a characteristic broad diffraction peak at 2θ=23°, indicating that they are amorphous non-crystalline glass structures; Figure 2 D is the Fourier transform infrared absorption spectrum (FTIR) of the bioactive glass. It can be seen that both weeks are at 1080 cm -1 and 800cm -1 The strong and broad absorption peaks are attributed to the asymmetric stretching vibration of Si-O-Si bond and the stretching and bending vibration of Si-O bond, which is a typical bioactive glass structure. Compared with BGNCu, BGNCu@EGCG has a strong absorption peak at 1636cm -1 , 1522cm -1 , 1466cm -1 A new absorption peak appears at , which can be attributed to the C═C stretching vibration on the benzene ring of EGCG.
[0064] Figure 3 EGCG loading rate and release curve of the bioactive glass prepared by the present invention. Figure 3 A is the thermogravimetric analysis (TGA) graph, from which it can be seen that the EGCG loading rate is 26.08%; Figure 3 B is the release curve of the drug EGCG over time under different pH environments (pH 7.4 or 5.5), indicating that the release of EGCG is pH responsive, and the cumulative release of EGCG is 36.7% (pH 5.5), which is significantly higher than 28.9% (pH 7.4).
[0065] Figure 4 It is the biocompatibility test result of the bioactive glass prepared by the present invention. Figure 4 A is the cell activity measurement after BGNCu and BGNCu@EGCG were co-cultured with human dental pulp stem cells (HDPSCs) at different concentrations for 24 h (*p<0.05); Figure 4 B is the hemolysis rate of BGNCu and BGNCu@EGCG at different concentrations after co-culture with rat red blood cells (RBCs) for 30 minutes (****p<0.0001). Figure 4A shows that when 25μg / mL nanospheres were co-cultured with HDPSCs for 24h, the cell viability of the BGNCu@EGCG group (approximately 109.7%) was significantly higher than that of the BGNCu group (approximately 95.7%) (p<0.05). The cell viability of 200μg / mL BGNCu co-cultured with HDPSCs for 24h (approximately 86.8%) was significantly lower than that of the Control group (p<0.05), indicating that EGCG modified BGNCu significantly improved cell compatibility. Figure 4 B shows that as the concentration of nanospheres gradually increased to 1000 μg / mL, the hemolysis rate of each group gradually increased. At 1000 μg / mL, the hemolysis rate of the BGNCu group (approximately 10.7%) was significantly higher than that of the BGNCu@EGCG group (approximately 3.9%) (p<0.0001), exceeding the safe hemolysis range (5%), indicating that EGCG-modified BGNCu significantly improved blood compatibility. In summary, compared with BGNCu, BGNCu@EGCG has better biosafety.
[0066] Figure 5 The X-ray diffraction patterns (XRD) of the bioactive glass desensitizer prepared by the present invention before and after being immersed in simulated body fluid (SBF) for different time periods (1, 3, 7, and 14 days). Figure 5 A is the XRD pattern of BGNCu before and after mineralization after immersion in SBF for different time periods; Figure 5 B is the XRD spectrum of BGNCu@EGCG before and after mineralization after soaking in SBF for different time periods. As can be seen from the figure, after soaking in SBF for two weeks, compared with BGNCu, the peaks of BGNCu@EGCG at 2θ=26° and 2θ=46° are stronger, representing higher crystallinity and stronger strength of hydroxyapatite (HAp) at the crystal planes (211) and (222). EGCG has high water solubility, so after modification with BGNCu, the water solubility of BGNCu@EGGC is improved, and it can fully contact with water molecules, so the degradation rate is faster. Therefore, the HAp characteristic peak intensity of BGNCu@EGGC after soaking in SBF for 2 weeks is higher, indicating that its biological activity is stronger.
[0067] Figure 6The following is a scanning electron microscope image of the sealing effect of the dentinal tubules treated with the bioactive glass desensitizer prepared by the present invention for one week. Among them, 6A is the dentinal tubules of the untreated group. It can be observed that the dentinal tubules of the control group are almost all open, with only a small amount of minerals deposited unevenly; 6B is the dentinal tubules treated with BGNCu. It can be observed that most of the dentinal tubules are blocked by microspheres, there are still a small number of open areas, and a large number of microspheres are not degraded; 6C is the dentinal tubules treated with BGNCu@EGCG. It can be observed that most of the dentinal tubules are sealed. 6D is the dentinal tubules of the untreated group after being soaked in 6% citric acid for 60 seconds. It can be observed that the diameter of the dentinal tubules in the control group is enlarged and all open; 6E is the dentinal tubules of the BGNCu group after the same treatment. It can be observed that the dentinal tubules are significantly enlarged and the original surface minerals are dissolved; 6F is the dentinal tubules of the BGNCu@EGCG group after the same treatment. It can be observed that the dentin surface is rough and the tubules are only slightly open. The above results show that BGNCu@EGCG has good acid resistance after treatment, which may be attributed to the fact that the released EGCG can inactivate matrix metalloproteinases, thereby preventing dentin collagen degradation and enhancing acid resistance stability. Therefore, compared with BGNCu, BGNCu@EGCG has better acid resistance stability as a dentin desensitizer. 6G is the dentinal tubules of the untreated group after mechanical abrasion by brushing. The thin layer of minerals deposited on the surface disappears, and a large number of dentinal tubules are open; 6H is the dentinal tubules of the BGNCu group after the same treatment. A large number of dentinal tubules are open and the surface is rough; 6I is the dentinal tubules of the BGNCu@EGCG group after the same treatment. Most of the tubules are blocked, and only part of them are slightly open, which has the best blocking effect. The above results show that BGNCu@EGCG has good wear resistance after treatment, which may be attributed to the fact that the released EGCG can act as a dentin collagen cross-linking agent to improve the mechanical properties of dentin. Therefore, compared with BGNCu, BGNCu@EGCG has better wear resistance stability as a dentin desensitizer.
[0068] Figure 7 This is the result of the bioactive glass nanoparticles prepared by the present invention inhibiting Streptococcus mutans. Figure 7 A is the image of the coated agar plate of the untreated group (BGN), BGNCu, BGNCu@EGCG (2 mg / mL) co-cultured with Streptococcus mutans for 24 h. It can be observed that the number of colonies on the plate of the BGNCu@EGCG group is the least. Figure 7 B is the quantitative counting image of colony forming units on the plate. Different lowercase letters indicate statistical differences (p<0.05). It can be seen from the figure that compared with BGNCu, BGNCu@EGCG has a stronger inhibitory effect on the growth of Streptococcus mutans, which can be reduced by half an order of magnitude.
[0069] Figure 8 This is a scanning electron microscope image of the biofilm formed by Streptococcus mutans on the dentinal tubules treated with the bioactive glass desensitizer prepared by the present invention. It can be observed that a large amount of thick biofilm adheres to the surface of dentin in the Control group (BGN), and the dentinal tubules are open; the total amount of Streptococcus mutans biofilm in the BGNCu group is greatly reduced, and a small amount of biofilm still covers the surface of the tubules. The total amount of Streptococcus mutans biofilm in the BGNCu@EGCG group is greatly reduced, and the dentinal tubules are stably blocked. It can be seen from the figure that as a dentin desensitizer, compared with the BGNCu desensitizer, the BGNCu@EGCG desensitizer has a better inhibitory effect on the formation of Streptococcus mutans biofilm, and is more suitable for use as a desensitizer in a real oral environment.
[0070] Depend on Figure 7 and Figure 8 It can be seen that copper-doped calcium phosphosilicon bioactive glass and PP surface-modified bioactive glass can effectively improve the antibacterial ability of bioactive glass, and the two show a synergistic effect.
[0071] In summary, the cost of raw materials required for the synthesis process of the present invention is low, such as copper nitrate and PP, which are easy to obtain and have great economic benefits; the method is simple in process and easy to operate in the preparation process, and the BGN particles are synthesized by the sol-gel method combined with the template method, and the BGNCu particles are prepared by the element copper as the doping ion, and then the PP is coated by the in-situ self-deposition method to prepare BGNCu@PP; the material has a stable structure, uniform particle size, high drug loading rate and release rate, and good biocompatibility; high biological activity, and obvious in vitro mineralization activity after immersion in simulated body fluid (SBF); it can effectively block the dentinal tubules, and has stable acid and wear resistance; it has a significant inhibitory effect on the formation of caries-causing bacteria (such as S.mutans) and biofilms, and shows great application potential in the treatment of dentin sensitivity. The prepared BGNCu@PP nanoparticles have a stable structure, high drug loading and release rate, good biocompatibility, acid and wear resistance stability, antibacterial properties, etc., and the prepared desensitizer has broad application prospects for the treatment of dentin sensitivity.
[0072] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A bioactive glass composition, characterized in that: include: A substrate, wherein the substrate is bioactive glass; The surface of the substrate is modified with polyphenol compounds.
2. The bioactive glass composition according to claim 1, characterized in that The bioactive glass is calcium phospho-silicon bioactive glass.
3. The bioactive glass composition according to claim 1, characterized in that The bioactive glass is copper-doped calcium-phosphorus-silicon bioactive glass.
4. The bioactive glass composition according to claim 3, characterized in that The molar ratio of silicon, calcium, phosphorus and copper in the copper-doped calcium-phosphorus-silicon bioactive glass is 60-90:35-5:4:1-5.
5. The bioactive glass composition according to claim 1, characterized in that The polyphenol compound is selected from at least one of epigallocatechin gallate, resveratrol and tannic acid.
6. A method for preparing a bioactive glass composition, characterized in that: include: The bioactive glass is dispersed in an alkaline buffer solution, and then added dropwise to a solution of a polyphenol compound, and the bioactive glass changes color to obtain the bioactive glass composition of claim 1.
7. The method for preparing the bioactive glass composition according to claim 6, characterized in that: The alkaline buffer solution is a tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 8 to 9.
8. The method for preparing the bioactive glass composition according to claim 6, characterized in that: The mass ratio of the bioactive glass to the polyphenol compound is 5:2-10.
9. Use of the bioactive glass composition according to any one of claims 1 to 5 in the preparation of a tooth desensitizing agent.
10. Use of the bioactive glass composition according to any one of claims 1 to 5 in the preparation of toothpaste additives.
Citation Information
Cited By
Antibacterial and anti-inflammatory regenerative pulp capping material and preparation method thereof
CN121015962A